'We know what is at stake'. (2nd May 2019) - Leitch, Neil
Abstract : Despite the PVI sector delivering 80 per cent of the nation's childcare, it was the maintained nursery sector that recently received a £24m funding boost. Is putting up parent fees now the last resort?